Circumscribed palmar hypokeratosis: Report of 2 new Ecuadorian cases, dermatoscopic description and brief literature review - Enrique Uraga; Annette Morán; Juan Carlos Garcés (Our Dermatology Online, 2016)
The circumscribed palmoplantar hypokeratosis (CPH) is a dermatosis that is unfrequently reported around the world. It predominantly affects middle to advanced aged women, involving acral skin, asymptomatic lesions, and of unknown cause. However, its´ clinical, histopathologic and dermoscopic characteristics are distinctive. We report two cases of female patients, who come for a medical consultation presenting a long-term lesion of several years, located on the palm, asymptomatic and with no apparent cause.